Blunt Abdominal Trauma in a European Trauma Setting: Need for Complex or Non-Complex Skills in Emergency Laparotomy. (June 2020) - Kosola, J.; Brinck, T.; Leppäniemi, A.; Handolin, L.
Background and Aims: Blunt abdominal trauma can lead to substantial organ injury and hemorrhage necessitating open abdominal surgery. Currently, the trend in surgeon training is shifting away from general surgery and the surgical treatment of blunt abdominal trauma patients is often done by sub-specialized surgeons. The aim of this study was to identify what emergency procedures are needed after blunt abdominal trauma and whether they can be performed with the skill set of a general surgeon. Materials and Methods: The records of blunt abdominal trauma patients requiring emergency laparotomy (n = 100) over the period 2006–2016 (Helsinki University Hospital Trauma Registry) were reviewed. The organ injuries and the complexity of the procedures were evaluated. Results: A total of 89 patients (no need for complex skills, NCS) were treated with the skill set of general surgeons while 11 patients required complex skills. Complex skills patients were more severely injured (New Injury Severity Score 56.4 vs 35.9, p < 0.001) and had a lower systolic blood pressure (mean: 89 vs 112, p = 0.044) and higher mean shock index (heart rate/systolic blood pressure: 1.43 vs 0.95, p = 0.012) on admission compared with NCS patients. The top three NCS procedures were splenectomy (n = 33), bowel repair (n = 31), and urinary bladder repair (n = 16). In patients requiring a complex procedure (CS), the bleeding site was the liver (n = 7) or a major blood vessel (n = 4). Conclusion: The majority of patients requiring emergency laparotomy can be managed with the skills of a general surgeon. Non-responder blunt abdominal trauma patients with positive ultrasound are highly likely to require complex skills. The future training of surgeons should concentrate on NCS procedures while at the same time recognizing those injuries requiring complex skills.